The impacts of shipping and related activities on ocean sustainability. A study into the various aspects to overcome global impacts - Chiang, Zi Yang (Nanyang Technological University, 2021)
Ocean sustainability have been increasing being brought out to the table for discussions. It has certainly gained much attention these few years with the rise of global temperatures due to climate changes. The maritime industry is not spared from the table as well. The impacts of shipping activities and its related activities are examined closely by the International Maritime Organisation (IMO). As a result, conventions aimed at reducing these impacts are being reviewed and reassessed to determine their effectiveness in sustainability of our oceans. Therefore, nations and shipping organisations are facing increasing pressures from stricter regulations implemented on an international level. This paper seeks to identify the impacts of shipping activities and the related activities on ocean sustainability. It will also analyse the regulations and their effectiveness concerning the industry. A study will also be done on the barriers to implement newer and more stringent regulations. Some proposals to reduce the impacts of the industry and allow the ease of implementing regulations will also be discussed under recommendations. This paper uses primarily interview responses from industry professionals and past studies on this topic to derive a meaningful and well – balanced research paper.